Potential impacts and demand for picture-based crop insurance: Qualitative research findings from Haryana state, India - Misra, Rewa S.; Ceballos, Francisco; Kannan, Samyuktha; Kramer, Berber (International Food Policy Research Institute, 2020)
This report summarizes results from qualitative research on a picture-based insurance solution to improve agricultural risk management. We conducted focus group discussions with 122 male and 77 female members of farming households in the state of Haryana in India. Participants perceive horticulture crops like tomato as high-risk, high-return investments. Excess rainfall, hail, and pests are considered key risks for both wheat and paddy farming, while disease and hail are identified as more important risks for tomato production. Respondents distrust insurance and there is widespread use of informal credit as a risk coping strategy. Female household members not involved in production have limited knowledge about investments in and returns from crops but are aware of price and production shocks as well as the coping strategies in response to these. In addition, households do not show sufficient knowledge of crop insurance as a coping mechanism. Smartphone penetration and use was found to be high among interviewed households, but women rarely own smartphones and rely instead on younger members of the household. Given households’ familiarity with credit and their distrust of insurance, credit and insurance bundles are a potential mechanism to encourage adoption of smartphone-based insurance solutions. Moreover, additional research is needed about female financial knowledge, attitudes towards risk and risk coping, and households’ demand for insurance.